2012
DOI: 10.1016/j.compfluid.2012.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Flow structures in cerebral aneurysms

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms AbstractMechanical properties of blood flow are commonly correlated to a wide range of cardiovascular diseases. In this work means to describe and characterise the flow field in the free-slip and no-slip domains are discussed in the context of cerebral aneurysms, reconstructed from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…21,22 However, the frequent need for a user supplied threshold to construct these surfaces led us to use line-type methods for visualizing and analyzing the spatial structure of hemodynamic flows. 23–26 Irregular aneurysm geometries make the task of identifying a “characteristic length” difficult and subjective. As a result, we used the unnormalized length.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 However, the frequent need for a user supplied threshold to construct these surfaces led us to use line-type methods for visualizing and analyzing the spatial structure of hemodynamic flows. 23–26 Irregular aneurysm geometries make the task of identifying a “characteristic length” difficult and subjective. As a result, we used the unnormalized length.…”
Section: Discussionmentioning
confidence: 99%
“…The fixed points that are of saddle-type (i.e their two eigenvalues are real and have different signs, and the eigenvectors are real) are identified. These fixed points are perturbed along the positive eigenvector (i.e., corresponding to the positive eigenvalue) in two opposite directions to obtain two initial conditions [22]. The WSS trajectories constructed from these initial conditions in forward time will trace out the unstable manifold.…”
Section: Wss Stable/unstable Manifoldsmentioning
confidence: 99%
“…The time step was chosen to divide the cardiac cycle (T = 0.88 s) into 5000 time steps. A cerebral aneurysm model used in a previous study [22] was remeshed with a higher mesh resolution (next to wall edge size of 100 µm). The same boundary conditions and parameters used in [22] were specified.…”
Section: Computational Fluid Dynamics (Cfd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies based on large patient cohorts have found that vortex core lines in ruptured aneurysms exhibit more temporal and spatial fluctuations [18,19]. Because vortex core lines only show the skeleton of the entire vortex structure, and identification of twodimensional planes can be subjective, the true association of vortical flow and IA rupture status remains unclear.…”
Section: Introductionmentioning
confidence: 99%